Auteurs des ouvrages recensés (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Éléments d’une stratégie de l’entreprise (Relations industrielles / Industrial Relations, 1971)
Réponse au conflit entre responsabilités économiques et responsabilités sociales : un défi aux dirigeants CENTRE DES DIRIGEANTS D'ENTREPRISE Quelque deux cents membres du Centre des Dirigeants d'Entreprise ont participé de diverses manières, à l'élaboration de ce document. Il a été largement discuté, et corrigé à plusieurs reprises. Il sera remis sur le métier et révisé progressivement, non par souci de purisme, mais parce qu'il s'agit d'un instrument de travail destiné à s'enrichir des expériences qu'il devrait susciter. Issu des études de plusieurs comités et assemblées régionales, il rassemble les éléments principaux d'un programme d'action portant sur une réforme de l'entreprise. Action d'autant plus nécessaire que la population se reconnaît de plus en plus difficilement dans une société en proie à des mouvements imprévus. Ce phénomène de rejet annonce ou accompagne les grands bouleversements politiques et sociaux. Des événements récents ont sonné, chez nous et ailleurs, la cloche d'alarme ; nous nous trouvons indiscutablement au point de départ de changements majeurs. Nul ne saurait prévoir si ces changements se feront dans la violence ou selon un autre mode d'évolution. Cependant, il suffit d'évoquer les programmes législatifs récents et d'être témoin des affrontements durables qui se déclarent autour de certains projets de loi, pour constater que la population est sérieusement divisée contre elle-même et pour en conclure que nos institutions, surtout l'entreprise privée, ne peuvent échapper à des chambardements très sérieux dont certains sont déjà en route. Ces perspectives n'ajouteront pas une once de discernement aux esprits placides, de tous milieux, motivés par la seule considération de leurs intérêts. Les dangers inhérents aux improvisations démagogiques n'empêcheront pas davantage les contestataires professionnels de pousser la population dans les aventures les plus risquées. Les mesures de salut reposent entre les mains d'individus répartis à proportions égales à travers les diverses classes de citoyens. Le texte qui suit s'adresse surtout aux hommes d'affaires qui considèrent une présence plus vigilante et plus active de l'entreprise comme une condition indispensable à l'orientation pacifique de la société ; il se résume en somme à deux propositions : • Prise de conscience aussi claire que possible de la situation ; • Engagement immédiat et précis dans une série d'interventions correctives et d'activités concertées, susceptibles d'accélérer l'intégration de l'entreprise dans le milieu économique et culturel. Confirmé par des commentaires et analyses émanant des milieux les plus divers, le diagnostic du *CDE ne peut manquer de serrer de près la réalité des événements actuels. Quant aux lignes d'action proposées, une simple observation attentive en justifie l'urgente nécessité. Il reste à savoir si les dirigeants d'entreprise sont disposés, en nombre suffisant, à poser les gestes qui leur permettront d'apporter une contribution efficace au progrès de la société. C'est une question de clairvoyance et de volonté; mais elle implique un abandon radical du laisser-faire et de l'indifférence traditionnels. JEAN BRUNELLE Directeur général Centre des Dirigeants d'Entreprise
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Index alphabétique des articles (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Index analytique des articles (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Index des auteurs d’articles et des recensions (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Index méthodique des articles (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Index méthodique des ouvrages recensés (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le Conseil consultatif du travail et de la main-d’oeuvre publie son rapport annuel (deuxième) pour l’année 1970-71. (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Références bibliographiques (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Wildcat Strike in Lake City - Anton, F. R. (Relations industrielles / Industrial Relations, 1971)
This article reviews the study "Wildcat Strike in Lake City" by Maxwell Flood.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Lexique du calcul économique et de l’économétrie - Autin, Claude (Relations industrielles / Industrial Relations, 1971)
This article reviews "Lexique du calcul économique et de l’économétrie" by André Olmi and Fortuné July.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

British Collective Bargaining : The Challenges of the 1970’s - Banks, Robert F. (Relations industrielles / Industrial Relations, 1971)
In the 1960's Britain’s traditional industry-wide collective bargaining system was modified significantly by the growth of local bargaining, the introduction of an incomes policy and government recommendations for the general reform of industrial relations. Other important innovations were long term agreements, status agreements and productivity bargaining. The Conservative Governments new Industrial Relations Act will have a significant impact on the industrial relations system, particularly with regard to union recognition, internal unions affairs and the protection of the rights of individual employees. However, the Acts restrictions on the right to strike are likely to have only a minimal impact on established bargaining relationships. As Great Britain enters the 1970's the industrial relations system's main challenge is for unions and management to voluntarily respond to the problems which continue to be posed by the uncoordinated growth of plant bargaining.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Trade-Unions in an Age of Pluralism and Structural Change : The Response to the Irrepressible Demands of the Common Man - Barkin, Solomon (Relations industrielles / Industrial Relations, 1971)
Reviewing the industrial unrest of the last three years in Western Europe and the United States, the author describes and analyses the new trends in the trade-union movement to cope with such a new situation.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Trends in Industrial Relations Systems of Continental Europe - Barkin, Solomon (Relations industrielles / Industrial Relations, 1971)
This article reviews "Trends in Industrial Relations Systems of Continental Europe" by Paul Malles.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

De la prévision économique à la gestion financière - Beaulieu, Jean-Pierre (Relations industrielles / Industrial Relations, 1971)
This article reviews "De la prévision économique à la gestion financière" by Jacques Gervais.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’audiovisuel au service de la formation, méthodes-matériels - Beaulieu, Jean-Pierre (Relations industrielles / Industrial Relations, 1971)
This article reviews "L’audiovisuel au service de la formation, méthodes-matériels" by Robinson P. Rigg.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La participation des travailleurs aux décisions dans les entreprises - Beaulieu, Jean-Pierre (Relations industrielles / Industrial Relations, 1971)
This article reviews "La participation des travailleurs aux décisions dans les entreprises" by the Bureau international du travail (Genève).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labor Economics and Labor Relations - Beaulieu, Jean-Pierre (Relations industrielles / Industrial Relations, 1971)
This article reviews "Labor Economics and Labor Relations" by Lloyd G. Reynolds.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le potentiel de développement des cadres - Beaulieu, Jean-Pierre (Relations industrielles / Industrial Relations, 1971)
This article reviews "Le potentiel de développement des cadres" by the Organisation interentreprise pour la coordination de la recherche sociale (Paris).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les Business School Américaines - Beaulieu, Jean-Pierre (Relations industrielles / Industrial Relations, 1971)
This article reviews "Les Business School Américaines" by Michel Chevalier and Jean François de Chorivit.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Social Psychology of the Work Organization, and Training in Industry : The Management of Learning - Beaulieu, Jean-Pierre (Relations industrielles / Industrial Relations, 1971)
This article reviews "Social Psychology of the Work Organization" by Arnold S. Tannenbaum, and "Training in Industry : The Management of Learning" by Bernard M. Bass and James A. Vaughan.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Comment concevoir un système intégré de gestion - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1971)
This article reviews "Comment concevoir un système intégré de gestion" by P. J. Yvon et C. Semin.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Industrial and Organizational Psychology - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1971)
This article reviews "Industrial and Organizational Psychology" by Abraham K. Korman.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’entretien d’appréciation : six dialogues entre chef et subordonné - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1971)
This article reviews "L’entretien d’appréciation : six dialogues entre chef et subordonné" par N.R. Maier.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les méthodes d’intégration dans l’entreprise à Grenoble - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1971)
This article reviews "Les méthodes d’intégration dans l’entreprise à Grenoble" by Colette Verlhac.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labor Economics - Belzile, Bertrand (Relations industrielles / Industrial Relations, 1971)
This article reviews "Labor Economics" by C.G. Williams.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Quantitative Analysis of Modernization and Development - Belzile, Bertrand (Relations industrielles / Industrial Relations, 1971)
This article reviews "Quantitative Analysis of Modernization and Development" by Frederick H. Harbizon, Joan Maruhnic and Jane R. Resnick.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Retour des femmes sur le marché du travail après interruption d’emploi - Belzile, Bertrand (Relations industrielles / Industrial Relations, 1971)
This article reviews "Retour des femmes sur le marché du travail après interruption d’emploi" by B.N. Sear.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Science and Society, The Meaning and Importance of Scientific Method - Bernier, Jean (Relations industrielles / Industrial Relations, 1971)
This article reviews "Science and Society, The Meaning and Importance of Scientific Method" by Michael Bassey.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Growth of White-Collar Unionism - Bernier, Jean (Relations industrielles / Industrial Relations, 1971)
This article reviews "The Growth of White-Collar Unionism" by George Sayers Bain.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’action politique du CTC et de la FAT-COI : une comparaison depuis 1956 - Boivin, Jean (Relations industrielles / Industrial Relations, 1971)
Dans cet article, l'auteur examine les relations qui existent entre le Congrès du travail du Canada et le Nouveau Parti Démocratique ainsi qu'entre la Fédération américaine du travail et le Parti Démocratique aux États-Unis. Après avoir souligné les principales caractéristiques de ces relations dans les deux pays, l'auteur procède à l'examen de trois facteurs majeurs pouvant expliquer les différences respectives. Dans une dernière partie, il tente d'évaluer le succès obtenu par chaque forme d'action politique.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Teachers vs School Board - Boivin, Jean (Relations industrielles / Industrial Relations, 1971)
This article reviews "Teachers vs School Board" by Donald J. Noone.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Labor Market Experience of Engineers in North America - Boyd, Archibald D.; Gross, Andrew C.; McKay, Raymond R. (Relations industrielles / Industrial Relations, 1971)
The authors have undertaken a major project which they envision ultimately as an on-going analysis of the labor market behavior of technical and scientific manpower in highly developed economies. Their paper represents a first step in this direction.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La négociation sectorielle : une panacée? - Brody, Bernard (Relations industrielles / Industrial Relations, 1971)
L'auteur commente l'article de Normand Cinq-Mars« Négociation locale et négociation sectorielle » Relations industrielles, volume 25, numéro 3, 1970.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le bilan de l’année 1970 en droit du travail français - Camerlynck, G. H. (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le rôle et les fonctions des centres de relations industrielles en France - Candau, Pierre (Relations industrielles / Industrial Relations, 1971)
Après une brève description des caractéristiques du système de relations industrielles en France et du rôle de l'Université, l'auteur présente les structures et l'organisation des Centres de relations industrielles en ce pays. Il insiste sur la recherche, l'enseignement et la formation dans ce domaine.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Canadian Graduate Theses : 1919-1967 : An Annoted Bibliography covering Economic Business and Industrial Relations - Cardin, Jean-Réal (Relations industrielles / Industrial Relations, 1971)
This article reviews "Canadian Graduate Theses : 1919-1967 : An Annoted Bibliography covering Economic Business and Industrial Relations" by W.D. Wood, L.A. Kelly and P. Kiemar.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Évolution du patronat et ses répercussions sur les attitudes et pratiques patronales dans la province de Québec - Cardin, Jean-Réal (Relations industrielles / Industrial Relations, 1971)
This article reviews the study "Évolution du patronat et ses répercussions sur les attitudes et pratiques patronales dans la province de Québec" by Laurent Bélanger, Ph.D.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le syndicalisme est-il la réponse au problème des « cadres »? - Chartier, Roger (Relations industrielles / Industrial Relations, 1971)
Après avoir souligné la modification relativement récente, en divers milieux québécois, des attitudes traditionnelles à l'endroit des« cadres » d'entreprise, l'auteur déplore la faiblesse lexicologique du terme« cadres » dans ce contexte, de même que l'ambiguïté de ce vocable globaliste, eu égard à la grande diversité des agents qu'il recouvre. A partir donc d'une esquisse de typologie des« cadres », il s'interroge ensuite sur leursproblèmes présumés ou réels— qu'il s'agisse plus largement d'« aliénation » ou plus spécifiquement de divers malaises concrètement identifiables à partir d'une échelle donnée de besoins. Pour chacun de ces problèmes, l'auteur examine enfin diversessolutions institutionnelles qui sont à la disposition des« cadres » : action patronale, association de cadres, syndicalisme de cadres et législation élargie.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Ontario’s Bill 167 : Reform of the Status Quo - Crispo, John H. G. (Relations industrielles / Industrial Relations, 1971)
This paper reviews the amendments made in 1970 in the Ontario Labour Relations Act, explains their consequences and comments on some of the serious omissions of the Bill 167.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’unité d’accréditation appropriée et la langue du travail : l’affaire de la Régionale Le Royer - D’Aoust, Claude (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’unité d’accréditation des professionnels - D’Aoust, Claude (Relations industrielles / Industrial Relations, 1971)
L'article 20 du Code du Travail et la syndicalisation des ingénieurs et autres scientifiques : le cas de la RCA LIMITED. En mars dernier, le Tribunal du travail rendait jugement dans une affaire où la principale question de droit reposait sur l'interprétation du troisième alinéa de l'article 20 du Code du Travail 1. Je me propose ici de commenter cet aspect de la décision. 1 RCA LIMITED (appelante) v. RCA Engineers and Scientists Association (intimée), décision de Monsieur le juge Filion, Tribunal du travail, 16 mars 1971, dossier no. M-70-D-95. En appel d'une décision du commissaire-enquêteur Devlin, 17 décembre 1970, dossier no. 1620-33.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le rôle de l’enquêteur dans le Code du Travail - D’Aoust, Claude (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le Code du travail : sa nature, sa portée, ses effets - Dion, Gérard (Relations industrielles / Industrial Relations, 1971)
This article reviews "Le Code du travail : sa nature, sa portée, ses effets" by Fernand Morin.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Psychologie du groupe - Dion, Gérard (Relations industrielles / Industrial Relations, 1971)
This article reviews "Psychologie du groupe" by M.A. Robert.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Répertoire des grèves dans la province de Québec au XIXe siècle - Dion, Gérard (Relations industrielles / Industrial Relations, 1971)
This article reviews "Répertoire des grèves dans la province de Québec au XIXe siècle" by Jean Hamelin, Paul Larocque and Jacques Rouillard.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Best of the Canadian Personnel Journal - Dion, Gérard (Relations industrielles / Industrial Relations, 1971)
This article reviews "The Best of the Canadian Personnel Journal" by J.R. Perigoe and T.F. Hercus.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Regional Unemployment Rates and Total Economic Growth in Canada, 1953-1968 - Donner, Arthur W. (Relations industrielles / Industrial Relations, 1971)
In this article the author tests the hypothesis that the process of general economic growth in Canada has an unequal impact on regional economic activity.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Centralized Collective Bargaining : U.S.-Canada Experience - Downie, Bryan M. (Relations industrielles / Industrial Relations, 1971)
The author is concerned with bi-national bargaining which entails the delegation of decision-making power from Canada to the United States either through adherence to a U.S. pattern or standard and/or through the actual delegation of decision-making power in collective bargaining to U.S. officials. This paper attempts to take an initial step in the direction of increasing our understanding of what generates bi-national arrangements, what tactics and strategies are involved, and the implications.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Industrial Conversion and Workers’ Attitudes to Change in Different Industries - Flood, Maxwell (Relations industrielles / Industrial Relations, 1971)
This article reviews the study "Industrial Conversion and Workers’ Attitudes to Change in Different Industries" by Jan J. Louser and Michael Fullan.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

American Transfer Policies : Costs and Benefits - Glueck, William F. (Relations industrielles / Industrial Relations, 1971)
This article reviews Canadian-American business relations, describes how Canadian can be affected by transfer policies, discusses the causes, the costs and benefits of this policy and examines some policy implications for personnel administration in Canada and the United States.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La médecine en mutation - Guy, Réjeane (Relations industrielles / Industrial Relations, 1971)
This article reviews "La médecine en mutation" by Dr Jacques Mététrier.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Extension and Feasibility of the Woods Report to the Developing Countries - Hameed, Syed M.A. (Relations industrielles / Industrial Relations, 1971)
This paper attempts to evaluate the adequacy of the theoretical model used in the Woods Task Force Report, explores the possibility of Us extension to the analysis of the comparative industrial relations systems and examines the feasibility of exporting certain elements of the Canadian industrial relations system to the developing countries.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La négociation sectorielle par décision de l’État : le cas de la construction au Québec - Hébert, Gérard (Relations industrielles / Industrial Relations, 1971)
L'auteur dégage les principaux traits de la nouvelle Loi des relations de travail dans l'industrie de la construction au Québec : il n'y aura qu'une seule négociation et une seule convention collective, au niveau régional ou provincial. La loi vise à assurer plus d'ordre et plus d'unité dans une industrie déchirée par de nombreuses tensions ; l'expérience des négociations de 1969, et bien davantage celle de 1970, ne sont guère encourageantes : jamais décret n'a soulevé autant de difficultés ; et les rivalités intersyndicales demeurent aussi profondes que jamais, surtout en matière de placement et de sécurité d'emploi. Cet article a été préparé en juin 1970 et février 1971.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Adaptation and Innovation in Wage Payment Systems in Canada - Ingerman, Sidney H. (Relations industrielles / Industrial Relations, 1971)
This article reviews the study "Adaptation and Innovation in Wage Payment Systems in Canada" by Jack Chernik.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labor Relations in Ontario Hospitals : A Question of Survival - Isbester, Fraser; Castle, Sandra (Relations industrielles / Industrial Relations, 1971)
The authors examine the sources of the prevalent unrest among Ontario Hospital employees. As the specific causes of the present situation are outlined separately, their inter-relationships are to be borne in mind.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Lumber Industry in British Columbia - Jamieson, Stuart Marshall (Relations industrielles / Industrial Relations, 1971)
The author stresses the point that multi-employer bargaining in a primary or resource-based industry is under some circumstances at least, quite different in character and consequences from its counterpart in other types of industries or other contexts. To illustrate his point, he presents the case of the B.C. Coast Lumber Industry.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labor Mobility : An Investment in Human Capital Approach - Kottis, Athena P. (Relations industrielles / Industrial Relations, 1971)
The paper presents an explanation of the economic factors behind the geographic, occupational and industrial mobility of labor by considering movement from one area, occupation, or industry to another as an investment in human capital, requiring the incurrence of a certain cost and making possible certain returns, which are subject to various degrees of risk and uncertainty. It shows that both the traditional neoclassical theory and the institutional models present an incomplete picture of the factors affecting the mobility of labor and concludes that the factors deemed relevant by both theories are equally important in explaining the mobility of labor.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Human Adjustment to Technological Change : An Economist’s View - Kruger, Arthur A. (Relations industrielles / Industrial Relations, 1971)
The focus of this paper is to examine how collective bargaining has attempted to cope with the problems of worker displacement and how these developments might indicate future trends in union-management relations as well as the limitations of collective bargaining.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

A Study of the effects of the $1.25 minimum wage under the Canada Labour (Standards) Code - Lafrenière, Jacques (Relations industrielles / Industrial Relations, 1971)
This article reviews "A Study of the effects of the $1.25 minimum wage under the Canada Labour (Standards) Code" by Mahmood A. Zaidi.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le syndicalisme au Québec : structure et mouvement - Lafrenière, Jacques (Relations industrielles / Industrial Relations, 1971)
This article reviews the study "Le syndicalisme au Québec : structure et mouvement" by MM. J. Dofny et P. Bernard.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Syndicalisme, consommation et société de consommation - Lafrenière, Jacques (Relations industrielles / Industrial Relations, 1971)
This article reviews the study "Syndicalisme, consommation et société de consommation" by Bernard Solasse.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

GAP Initiation pratique - Langevin, Jean-Louis (Relations industrielles / Industrial Relations, 1971)
This article reviews "GAP Initiation pratique" par Dominique Lamure.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Unfair Labour Practices : An Explanatory Study of the Efficacy of the Law of Unfair Labour Practices in Canada - Lorentsen, Edith (Relations industrielles / Industrial Relations, 1971)
This article reviews the study "Unfair Labour Practices : An Explanatory Study of the Efficacy of the Law of Unfair Labour Practices in Canada" by Inis Christie and Morly Gorsky.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Multinational Corporation and Industrial Relations : The European Approach - Malles, Paul (Relations industrielles / Industrial Relations, 1971)
The author considers whether the multinational corporation constituted a challenge to the industrial relations systems as they have developed in Europe over the last quarter of a century and what response such a challenge found in the trade-union movement.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Trucking Industry in Ontario - McKechnie, Graeme (Relations industrielles / Industrial Relations, 1971)
In this case study of the Ontario trucking industry, the author considers the « for hire » section of the industry and, within this section, emphasizes general freight transport in order to illustrate the advantages and shortcomings of the multi-employer bargaining system.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Job Vacancy Survey as a Tool of Labour Market Information in Developing Countries - Mehmet, Ozay (Relations industrielles / Industrial Relations, 1971)
The purpose of this article is to present an operational method for collecting systematic data about current manpower demand. This method was originally developed in Malaysia, where it is now being implemented as a regular programme in the Ministry of Labour.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Structural Unemployment Theory and Measurement - Mehmet, Ozay (Relations industrielles / Industrial Relations, 1971)
This article reviews "Structural Unemployment Theory and Measurement" by G. Peter Penz.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Decentralized Bargaining : Its Problems and Direction in Ontario and the Western Provinces - Muir, J. Douglas (Relations industrielles / Industrial Relations, 1971)
This paper is directed to the bargaining structure issue and examines the problems and direction of decentralized bargaining in British Columbia, Alberta and Ontario.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

A Countercyclical Training Programme for Canada - Newton, Keith (Relations industrielles / Industrial Relations, 1971)
The author examines the current interest in the potential role of manpower policy as a stabilizing instrument and, more specifically, the contribution of one component : adult training programmes.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le rôle de la recherche dans la négociation collective centralisée - Quinet, Félix (Relations industrielles / Industrial Relations, 1971)
Après quelques commentaires sur le rôle de la recherche en négociation collective, l'auteur examine le contexte des négociations collectives au sein duquel fonctionne le Bureau de recherches sur les traitements.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les conventions collectives et leurs clauses d’ancienneté - Quinet, Félix (Relations industrielles / Industrial Relations, 1971)
En plus d'essayer de décrire ce qu'est la convention collective au Canada, l'auteur examine plus spécifiquement les clauses d'ancienneté, leur contenu et leur fréquence statistique pour certains secteurs.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Investment-Wages : Theory and Application - Reber, Gerhard (Relations industrielles / Industrial Relations, 1971)
After having defined and explained the goals of investment-wages, the author establishes their social and economic framework and gives an example drawn from the West-German construction industry.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

An Economic Critique of Current Technological Change Displacement Techniques - Ross, David P. (Relations industrielles / Industrial Relations, 1971)
This study attempts to assess how effective are the present methods employed by private parties for adjusting workers to technological change ; and effective is defined on the basis of the loss that displaced workers are expected to incur. The major conclusion is that if provisions such as advance notice, severance pay, attrition, seniority and bumping, early retirement, reduced work week, joint committees, and retraining are performing effectively it is largely the result of luck and circumstance

Reopeners : The Task Force on Labour Relations, and Freedman - Ross, David Philip (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Blue-Collarite - Roy, André (Relations industrielles / Industrial Relations, 1971)
This article reviews "Blue-Collarite" by Arthur B. Shostak.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Economic Consultative Bodies : Their Origins and Institutional Characteristics - Roy, André (Relations industrielles / Industrial Relations, 1971)
This article reviews "Economic Consultative Bodies : Their Origins and Institutional Characteristics" by Paul Malles, edited by Information Canada.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Flexibilité de l’âge de la retraite - Roy, André (Relations industrielles / Industrial Relations, 1971)
This article reviews "Flexibilité de l’âge de la retraite" a study published by l’organisation de coopération et de développement économique (Paris).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

GOMPERS - Roy, André (Relations industrielles / Industrial Relations, 1971)
This article reviews "GOMPERS" edited by Gérard Emmanuel Stern.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labor-Management Relations in the Public Service - Roy, André (Relations industrielles / Industrial Relations, 1971)
This article reviews "Labor-Management Relations in the Public Service" by Harold S. Roberts.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Emerging Worker - Roy, André (Relations industrielles / Industrial Relations, 1971)
This article reviews "The Emerging Worker" (Equality and Conflicts in the Mass Consumption Society) by William and Margaret Westley.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Valeurs économiques et valeurs juridiques dans les fusions d’entreprises - Roy, André (Relations industrielles / Industrial Relations, 1971)
This article reviews "Valeurs économiques et valeurs juridiques dans les fusions d’entreprises" by Philippe Comte.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Western European Labor and the American Corporation - Roy, André (Relations industrielles / Industrial Relations, 1971)
This article reviews "Western European Labor and the American Corporation" edited by Alfred Kamin.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Chronologie de la législation canadienne des relations de travail - Roy, Danielle (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les deux sexes dans la fonction publique - Sartin, Pierrette (Relations industrielles / Industrial Relations, 1971)
This article reviews "Les deux sexes dans la fonction publique" by Kathleen Archibald.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Problèmes posés dans l’entreprise par l’éclairage des locaux - Sartin, Pierrette (Relations industrielles / Industrial Relations, 1971)
L'auteur établit l'importance de l'éclairage dans la production, définit la lumière du jour comme l'idéal à atteindre et admet la nécessité de recourir aux installations artificielles pour lesquelles elle établit un certain nombre de facteurs à prendre en considération.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La négociation collective sectorielle - Sauvé, Robert (Relations industrielles / Industrial Relations, 1971)
Après avoir défini ce qu'il entend par négociation sectorielle, l'auteur admet que la négociation par établissement ne suffit plus à la tâche. C'est pourquoi il considère la négociation sectorielle comme étant fort désirable malgré un certain nombre de difficultés. Il conclut que le succès ou l'échec des négociations sectorielles tiennent bien moins aux structures légales qu'à la bonne foi des parties.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Cost-Benefit Analysis and the Economics of Investment in Human Resources : an Annotated Bibliography - Sexton, Jean (Relations industrielles / Industrial Relations, 1971)
This article reviews "Cost-Benefit Analysis and the Economics of Investment in Human Resources : an Annotated Bibliography" by W.W. Wood and H.F. Campbell.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Évaluation d’un programme de formation professionnelle - Sexton, Jean (Relations industrielles / Industrial Relations, 1971)
L'auteur tente d'évaluer le programme de formation professionnelle mis sur pied par le Comité de reclassement des travailleurs de la Coopérative fédérée de Québec {filialeLegrade Inc.).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Unemployed : A Social-Psychological Portrait - Sexton, Jean (Relations industrielles / Industrial Relations, 1971)
This article reviews "The Unemployed : A Social-Psychological Portrait" by D.W. Tiffany, J.R. Cowan and P.M. Tiffany.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Dictionnaire des partis communistes et des mouvements révolutionnaires - Solasse, Bernard (Relations industrielles / Industrial Relations, 1971)
This article reviews "Dictionnaire des partis communistes et des mouvements révolutionnaires" by François Fejtö.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Economic of Employee Benefits - Swidinsky, Robert (Relations industrielles / Industrial Relations, 1971)
This paper explores some of the factors determining the relative magnitude of select wage supplements. While the first section provides some insights into the nature and magnitude of all wage supplements in Canadian industries, subsequent sections are limited to the analysis of private employee benefit plans, their determinants and of their determining factors.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Judicial Review of Labour Arbitration in Ontario - Thompson, Mark (Relations industrielles / Industrial Relations, 1971)
Courts in Ontario have been increasingly willing to quash grievance arbitration awards. This article analyses the services of this conflict between the judiciary and arbitrators, the role the courts have assumed because of the compulsory use of arbitration, and the judges' reliance on precedent established British commercial arbitration. Most Ontario cases have involved one of four issues — evidence of intent, procedural violations of grievance clauses, disciplinary penalties, and denial of natural justice. In the first three areas especially, the courts have favoured narrow interpretations of collective agreements, limiting arbitrators' jurisdiction. This problem illustrates the difficulty in attempting to legislate a complex institution like grievance arbitration based on foreign experience, i.e. the United States.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Compulsory Arbitration in British Columbia : Bill 33 - Tsong, Peter Z.W. (Relations industrielles / Industrial Relations, 1971)
The author presents the reasons for the introduction of Bill 33 in British Columbia, examines the disputes which were settled under it, evaluates its impact on the frequency and the duration of work stoppages, and its role in the future of labour management relations in this province.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le Livre blanc sur l’assurance-chômage : une évaluation - Valcin, Yvon (Relations industrielles / Industrial Relations, 1971)
En plus d'une appréciation générale, l'auteur examine quelques points spécifiques du Livre blanc sur l'assurance-chômage.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’embauchage d’un salarié lié par une convention collective - Verge, Pierre (Relations industrielles / Industrial Relations, 1971)
L'embauchage d'un salarié lié par une convention collective peut-il être assorti de conditions particulières, non contenues dans celle-ci ? Dans l'affirmative, dans quelle mesure l'arbitre des griefs peut-il tenir compte d'un telle entente particulière ?
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La violation de la convention collective peut-elle donner ouverture à des dommages-intérêts? - Verge, Pierre (Relations industrielles / Industrial Relations, 1971)
L'exécution en nature de la convention collective n'étant pas toujours praticable, l'octroi d'une compensation pécuniaire peut être la seule façon de faire justice. Cette réponse affirmative pose le problème de la détermination de l'instance habilitée à ordonner le paiement de dommages-intérêts.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le caractère majoritaire des principes d’accréditation - Verge, Pierre (Relations industrielles / Industrial Relations, 1971)
La Cour suprême du Canada, réaffirmant le droit du syndicat majoritaire à l'accréditation, ordonne celle-ci, relativement à deux de trois groupes distincts établis par l'autorité compétente à partir d'une demande qui visait initialement l'ensemble des salariés de l'employeur 1 1 Association internationale des commis du détail, FAT -CIO -CTC, local 486v. Commission des relations de travail du Québec et Cie Paquet Inc.,arrêt unanime de la Cour suprême en date du 27 avril 1971.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Legal Status of Collective Agreements in England, the United States and Canada - Verge, Pierre (Relations industrielles / Industrial Relations, 1971)
This article reviews "The Legal Status of Collective Agreements in England, the United States and Canada" by B.L. Adell.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The British Industrial Relations Bill – An Analysis - Whittingham, T. G.; Towers, B. (Relations industrielles / Industrial Relations, 1971)
In this paper, the authors attempt to analyse the government intention and to assess some of the possible implications of the proposed measures in the British government's industrial relations Bill passed on December 8, 1970.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Collective Bargaining and Wage Equalization in Canada’s Iron & Steel Industry, 1939-1964 - Williams, Bryan C. (Relations industrielles / Industrial Relations, 1971)
This paper is one in a series being prepared by the Labour-Management Section of the Federal Department of Labour's Economies and Research Branch. It has three purposes. First, to highlight significant developments and characteristics in collective bargaining in the industry. Second, to determine the extent to which wage equalization is present in the industry. Third, to identify the influences that have contributed to these equalizing tendencies.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Some Comments on the Task Force on Labour Relations and Freedman : A Reply to David P. Ross - Woods, H. D. (Relations industrielles / Industrial Relations, 1971)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z